Electoral systems and their role in distributing seats: an analytical study (قضايا سياسية, 2024)
This research provides an in-depth analysis of electoral systems and seat allocation mechanisms, highlighting their role in ensuring representative justice and stabilizing democratic systems. The study focuses on defining electoral systems as the legal and institutional frameworks that regulate the process of electing representatives, emphasizing their role in shaping political orientations and establishing balances within legislative institutions.The research examines various types of electoral systems, such as proportional representation and majority systems, analyzing the mechanisms by which voters' preferences are converted into parliamentary seats. It also addresses different methods of seat allocation, including variable and fixed electoral quotients, showcasing the impact of these methods on election outcomes and their ability to ensure fair representation for diverse political and social forces.The study highlights the challenges facing electoral systems, including the complexities of seat allocation and their effect on political stability. It offers a critical evaluation of the extent to which these systems achieve democratic objectives by balancing equitable representation with effective governance, reflecting the growing importance of studying electoral systems in light of rapidly evolving political landscapes.